Critical discourse analysis on nomophobie students at in private university - Setyawan, Agustinus Hary; Hartati, Elysa ((JELE) Journal Of English Language and Education, 2018)
Nomophobie students have a major concern for current academic issues. Most mobile phone addiction is correlated with negative impacts. Hence, it is needed another descriptive result to know the whole impacts of nomophobie.The aim of this research is to know the critical discourse anlaysis for macro structure, superstructure, micro structure of the news articles by nomophobie students. This is a descriptive qualitative research of case studies which requires an exploratory method to examine, analyze and uncover certain cases. Â This research was conducted at a private university in Yogyakarta during January - September 2018. The ability of smartphone users' discourse analysis to circulate news about New Yogyakarta International Airport in two articles has been known in several elements. The findings show that theme elements has been 100% known by the nomophobie students. The second is the rethoric elements which is 91.6%. The third is stylistics which is known for 41.6%. The fourth is syntax which is 16.6%. Scheme and Semantics have not been known at all (9%) by the nomophobie students. Thus, it was proven that all nomophobie students always bring negative impacts towards a certain issue.